Hubungan Pengetahuan Tentang Personal Hygiene Dengan Penyembuhan Robekan Perineum Di Klinik Pratama Batang Jambu Desa Sidodadi Medan Tahun 2023 - Erwita Sari; Khairunnisa Situmorang; Eva Ratna Dewi; Parningotan Simanjuntak (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Postpartum infections, such as sepsis, are still the main cause of maternal death in developing countries. This study aims to determine the relationship between knowledge about personal hygiene and perineal wound healing in post-partum mothers at the Batang Jambu Pratama Clinic, Sidodadi Village in 2023. The research method used is an analytical survey with a cross-sectional approach. The population was all 32 post partum mothers with birth canal lacerations, and all of them were used as research samples. The results of the research show that there is a relationship between knowledge about personal hygiene and healing of perineal wounds in post-partum mothers, seen from the results of the chi-square test, which showed a p value of 0.003 < 0.005. It is hoped that health workers at the Batang Jambu Pratama Clinic will provide counseling to post partum mothers about personal hygiene so that mothers get information about how to carry out personal hygiene correctly so that perineal wounds can heal in <6 days.